THE ROLE AND IMPORTANCE OF ALISHER NAVAI'S WISE SAYINGS IN EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article highlights the issue of study of Alisher Navai’s wise words at literature lessons in a secondary school. It is noted that it is important to acquaint students with the life of the poet, who is the King of the Ghazali genre. Some of given samples of Alisher Navai’s wise sayings are analyzed. Those are   designed for grades 5-9 of high school.